Identification of High Delay Links in Internet Service Providers - Nobre, Francisco Valderlan; Santos, Danielle; Ribeiro, Silvio; Mesquita, Maria; Gomes, Rafael Lopes; Araújo, Thelmo (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC); 2023: Anais Estendidos do XII Latin-American Symposium on Dependable Computing, 2023)
Numerous companies and Internet Service Providers (ISPs) offer network monitoring services that include regular performance tests, with end-to-end delay being a critical piece of information they provide. Nevertheless, the monitoring tools still need to evolve in order to encompass more complex activities, such as high-delay detection. Within this context, this paper presents a method to detect high delays in communication links in the network infrastructure using the proposed Impact Score, based on data correlation techniques, over data from network monitoring tools. The experiments, using real data from the National Education and Research Network (RNP), show that the proposed method is capable of indicating the network links that compromise the end-to-end delay.